EL CARIOTIPO DE CHAETANTHERA INCANA POEPP. EX LESS. (ASTERACEAE) - Baeza, Carlos M.; Ruiz , Eduardo; Negritto, María A. (Gayana Botánica, 2008)
The karyotype of Chaetanthera incana Poepp. ex Less. from Chile was examined. This species belong to the subgenus Chaetanthera. The species has 2n = 2x = 22 chromosomes, with 10m + 1sm chromosomes. The reported karyotype is symmetric (AsI % = 56.0). These results were compared with Ch. chilensis and Ch. ciliata.